Prevalence, Knowledge and Practice of Self-Medication among Albanian Students of Medical Sciences - Rezarta Shkreli; Klodiola Dhamo; Afrim Tabaku (Advanced Concepts in Pharmaceutical Research Vol. 9, 2024)
The aim of the study was to determine the prevalence, knowledge and practice of self-medication among students in an Albanian Medical University. Self-medication is one of the most practiced worldwide issues and can cause both benefits and also side effects at a time when is not properly mentored by drug experts. The prevalence of self-medication is higher in developing countries and is on the rise globally. It is common in countries where it is easier to purchase prescription drugs without prescriptions and where the laws and regulations governing pharmacy practice are not followed under the pertinent guidelines. A cross-sectional survey on self-medication was conducted among students of medical sciences, with a standardized and structured questionnaire distributed to a total of 250 students attending the third-fifth year of pharmacy and dentistry as well as the first-third year of nursing. The prevalence of self-medication has resulted in 79.3%. Principal morbidities for seeking self-medication were headache 31.5%, flu/cold/cough 39.4% and fever 23.8%. Regarding the major reasons for seeking self-medication, previous experience with health problems 45.9%, mild illness 35.9%, knowledge about the drug and disease 18.2% and self-decision 15.5%. The most used medicines were NSAIDs (analgesics and antipyretics) 44.2%, antibiotics 34.8%, and antihistamines 13.3%. The strength of this survey which is the first study carried out in Albania, is that it provides baseline information on self-care and self-medication among Albanian medical students. According to this survey, the source of information for self-medication was previous experience 35.6%, previous prescription 34.7% and consulting with pharmacists 17.1%. The survey results indicate a high prevalence of self-medication among the students. There is an urgent need to enforce the law on over-the-counter drug sales and to educate the youth to ensure safe practices. Future studies might compare knowledge level, perception and practice of self-medication among medical students in different medical universities, with our results, to provide a more comprehensive overview of self-medication practice.